ANALISIS PRODUKTIVITAS TENAGA KERJA PEKERJAAN BALOK DAN PLAT LANTAI DENGAN METODE WORK SAMPLING - Mulyadi Sugih Dharsono; Siti Hindun (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Productivity is a crucial parameter in achieving project objectives. This research aims to obtain the value of labor productivity on the beam structure and floor plate in home construction using the work sampling method and analyze the comparison of the labor coefficient to the Analysis of Unit Price of Work (AHSP) in 2022. Experimental quantitative research describes this approach, utilizing information gathered through documentation, questionnaires, and participant observation. Data analysis in this research includes Data Uniformity Analysis, Data Sufficiency Analysis, Labor Utilization Rate (LUR), and Spearman Correlation. The findings revealed that the beam concreting job in home construction achieved a labor productivity rate (LUR) of 61.61% and 84.417 kg/person. In the floor plate concreting work, labor productivity reached 98.787 kg/person with a LUR value of 54.10%. Meanwhile, in formwork work, labor productivity reached 3.577 m/person with a LUR value of 53.37%, and in casting work, labor productivity reached 1.287 m/hour with a LUR value of 53.37%. Correlation analysis shows a positive relationship between Labor Utilization Rate and labor coefficient in concreting and formwork works. This indicates that the more efficient the labor, the higher the productivity in carrying out these activities, and the smaller the coefficient value obtained